Erwin Deutsch, the Eppinger Clinic and the legacy of the Second Vienna School of Medicine—Continuities of a career - Jobst, Clemens; Czech, Herwig (Wiener Klinische Wochenschrift, 2024)
Summary Erwin Deutsch (1917–1992) was an outstanding representative of Austrian internal medicine after World War II. Little is known about his early biography. Considered a “Jewish half-breed” under Nazi racial laws, he was subjected to harassment during his training. Nevertheless, he can be regarded as scientific heir of Hans Eppinger (1879–1946), who enjoyed a worldwide reputation as internist despite his controversial involvement in medical experiments in the Dachau concentration camp. Already declining after World War I, the Viennese Medical Faculty largely lost its international scientific importance with the expulsion of over half its faculty members from 1938, the end of the Second Vienna School of Medicine. Erwin Deutsch significantly contributed to continuity by vehemently calling for the unity of internal medicine after 1945, as it had been practiced in Vienna since the nineteenth century. Discrimination as a “Jewish half-breed” played a paradoxical role in this context—it delayed the start of his independent academic activity and increased his personal dependence on Eppinger; at the same time it spared him military service and enabled him to start his career after 1945 unaffected by denazification measures. Based on unpublished archival material, interviews with contemporary witnesses, and Deutsch’s medical publications, this article is the first to offer an account of his early career, from his graduation in 1940, his time at the Eppinger Clinic, compulsory service in Germany during the war and the beginning of his scientific work to his appointment as Ernst Lauda’s successor as director of the 1st Medical Clinic in Vienna.